Archeologický průzkum pusté rekreační chaty v Krkonoších - Lukáš Funk; Martin Váňa (AntropoWebzin)
There is a deserted recreational cottage called „Jelení louky“ near the town of Pec pod Sněžkou in the Krkonoše. This cottage is special because it has been left almost untouched and in a well-preserved state. The cottage was built in the first half of the 19th century and was abandoned in 1998. This spring, an archaeologist from the Department of Archaeology at the University of West Bohemia conducted archaeological research on the site. The research focused on the formation processes of archaeological record and on the cottage’s life.